Robot-assisted renal denervation as a new surgical approach for therapy resistant arterial hypertension - Sarah Rosier; Robby Lamoury; Koen Ameloot; Robbe Knaepen; Thomas De Sutter; Hans Goethuys; Yannic Raskin (Urology Case Reports)
Arterial hypertension is a major cause of mortality and morbidity worldwide. Medical therapy is the most common treatment. However, in some cases there is a persistent high blood pressure despite medical therapy. These patients with medication refractory arterial hypertension can be treated by renal denervation. Until now an endovascular approach has been used. There are however limitations in eligibility based on vascular or anatomical anomalies. For these patients, as well as other patients eligible for renal denervation, robot-assisted renal denervation has the potential to become a surgical treatment option based on our findings.